Ethnic diversity in UK bioscience: Structural biases and recommendations for action - Yusra Siddiqui; Prachi Stafford; Emmanuel Adukwu; Nicholas Freestone; Lovleen Tina Joshi; Emma Yhnell; Katharine Hubbard (PLoS ONE, 2025)
Scientific research is more innovative and impactful when scientists are drawn from diverse backgrounds. However, the scientific community does not reflect the demographics of wider society. Global Majority communities remain underrepresented within science, particularly within senior leadership roles. Here we explore ethnic diversity within UK academic biosciences, using publicly available staff and student demographic data from the UK Higher Education Statistics Authority. We use the Simpson index as a quantitative measure of diversity within the biosciences and construct linear mixed effect models to identify significant predictors of both student and staff ethnic diversity. For staff, there were significant negative effects on diversity for those in teaching-only roles, and lower diversity amongst higher paid and professorial or senior management staff. For students there are significant negative effects on diversity for part-time students and for postgraduate research students, with PhD students significantly less diverse than undergraduates. There was also considerable variation in diversity by biology subdiscipline, with higher ethnic diversity amongst biomedical sciences and biomolecular subdisciplines, while very low ethnic diversity was found within zoology, plant science and ecology. A correlation was found between the ethnic diversity of bioscience subdisciplines and the diversity of institutions offering those subdisciplines. Based on these findings, we provide evidence-based recommendations for action at various levels, including teaching teams, research groups, bioscience departments and professional bodies. We call upon the sector to take decisive steps to enhance outcomes and experiences for Global Majority staff and students, ultimately diversifying the academic pipeline to the direct benefit of UK bioscience.